IoTbased smart and flexible lightning in streets - Anitha, Raju; Nishitha, M; Akhila, K; Sai Anusha, K; Srilekha, G (International Journal of Engineering and Technology, 2018)
The internet of Things (IOT) is always giving unprecedented answers for the customary issues looked by man.One of the real obstacles in city is we are spending huge expenses on street light.Â To control the street lights based on detection of sunlight by implemented with smart embedded system. The paper is mainly utilized for smart and climate adaptive lighting in street lights. The street lights are automatically ON during the evening time and automatically OFF during day time.The street light can be accessed to turn ON or OFF at anyplace and anytime through web.In addition to that On top of the street light we are placing camera to track the activities performed on the street and where the recordings are stored in a server. Furthermore a panic button is placed on the pole, If there is any emergency situations like harassment, robbery there is a panic button is available at the reachable height any person can press it if he is in danger. If people are unable to press the panic button, they should use voice recognition which is connected to panic button, when it recognises some commands like help, it automatically press the panic button. Whenever the panic button is pressed, the footages at that time recorded by the camera is sent straightforwardly to the cloud account. The near specific police headquarters can have access of the account by which they can see the incidentâ€™s spot. Every region's street lights are associated with the specific area's police headquarters and cloud account can be accessible by each of them. Here GSMTechnology is eliminated completely.Safety and energy consumptions can be ensured by this idea.